Bacterial metagenome profiling of hand-made herby cheese samples utilizing high-throughput sequencing to detect geographical indication and marketing potential - Rustemoglu, Mustafa; Erkan, Mehmet Emin; Cengiz, Gazal; Hajyzadeh, Mortaza (Cell Press, 2023)
Food safety has been a major concern for consumers. Origin of food products matter for con-sumers such that the quality, reputation, or other special characteristics can be attributed essentially to that origin. While a geographical indication informs consumers for the origin of the product, it develops a competitive advantage for the markets. To detect distinguishing features of dairy products, the microbial composition of its microbiota is one of the emerging areas of in-terest. Utilizing novel approaches such as Next Generation Sequencing (NGS) technology to decipher the genetic code of 16s rRNA genes to characterize the bacterial population is widely applied. The bacterial microbiota of the herby cheese samples which were collected from S,irnak province in the South Eastern region of Turkey was examined by an NGS approach for purpose of finding geographical indication possibilities. In brief, Firmicutes is the dominant phyla where Lactobacillaceae and Streptococcaceae are abundant families across the analyzed herby cheese microbiota. The most prominent species is Companilactobacillus ginsenosidimutans detected as the dominant member of the bacterial consortia in 16 herby cheese samples. Another remarkable finding reported here is the Weissella jogaejeotgali which was detected in 15 cheese samples. Albeit the abundance of Levilactobacillus koreensis is low at the microbiome level it was identified in four herby cheese samples. As expected, lactic acid bacteria such as Lactobacillus delbrueckii, Lacto-coccus raffinolactis and Tetragenococcus halophilus were also identified. On the other hand, bac-terial diversity and microbial composition among cheese samples are not significantly affected by mixing different herbs on the manufacturing of herby cheeses. To the best of our knowledge, C. ginsenosidimutans, W. jogaejeotgali and L. koreensis are identified and reported for the first time in a dairy product and the bacterial richness and evenness of herby cheese are higher than those of most other cheeses. These findings make the cheeses in the geography where the samples were produced more valuable and provide opportunities for them to receive geographical indications. Thus, it will create added value while marketing the products.
Keywords: Herby cheese; Turkey; Companilactobacillus ginsenosidimutans; Microbiota; Geographical indications; NGS